Efecto de la concentración de ácido fluorhídrico sobre el ángulo de contacto de silanos de uno y dos pasos en cerámica de disilicato de litio - Maime Herrera, Mariella Antonieta (2021)
Objetive: To evaluate the contact angle of the silane of one and two steps in a disilicate ceramic with three concentrations of hydrofluoric acid. Materials and methods: Were used 36 ceramic blocks and it was divided into two groups: group with one- and two-step silane, and with hydrofluoric acid concentrations at 5%, 9% and 10% respectively. To evaluate the contact angle, a silane drop was placed in the center of the previously etched ceramics and later using photographic techniques, images of the drop were obtained to analyze them in an Image J software. Results: In a surface treatment with one-step silane and hydrofluoric acid at 5%, 9% and 10%, the contact angles obtained significant difference. With two-step silane, the surface treatment with 9% hydrofluoric acid showed a significant difference with respect to the contact angle between the 5% and 10% hydrofluoric acid concentrations. Conclusion: In the surface treatment with 10% hydrofluoric acid and one-step silane, a smaller contact angle was shown and with two-step silane, a smaller contact angle was shown with the 5% and 10 % hydrofluoric acid concentration.